ANALISIS FAKTOR-FAKTOR PENERIMAAN TEKNOLOGI TERHADAP PENGGUNAAN APLIKASI BSGTOUCH MENGGUNAKAN MODEL UTAUT2 - Miskiyah Nur Wahidah Balu; Irving Vitra Paputungan (LPPM Universitas Abdurrab, 2026)
The development of information technology has driven the transformation of banking services toward digital platforms, including BSGTouch, a mobile banking application developed by Bank SulutGo. Despite offering various banking services, BSGTouch still faces challenges such as limited features, an impractical account reactivation process, and user complaints that may affect technology acceptance and application usage. This study analyzes factors influencing the acceptance and use of BSGTouch using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. A quantitative survey was conducted with 183 active BSGTouch users in Gorontalo Province selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that Social Influence, Price Value, and Habit positively and significantly affect Behavioral Intention. Facilitating Conditions, Habit, and Behavioral Intention also positively and significantly affect Use Behavior. In contrast, Performance Expectancy, Facilitating Conditions, and Hedonic Motivation do not significantly affect Behavioral Intention, while Effort Expectancy has a significant negative effect. Habit is the most influential factor affecting Behavioral Intention. These findings provide insights for Bank SulutGo to improve service quality, enhance application features, and increase user acceptance and continued use of BSGTouch.